2018
DOI: 10.20944/preprints201808.0146.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A New Synthetic Histone Deacetylase Inhibitor, MHY2256, Induces Apoptosis and Autophagy Cell Death in Endometrial Cancer Cells via p53 Acetylation

Abstract: We previously found a novel a new sirtuin (SIRT) inhibitor MHY2256 that exerts anticancer activity through p53 acetylation in MCF-7 human breast cancer cells. Here, we investigated the anticancer activity of MHY2256 against hormone-related cancer, which is an endometrial cancer with poor prognosis. We found that MHY2256 markedly reduced cellular proliferation at low concentrations against Ishikawa endometrial cancer cells. The IC50 values of MHY2256 were much lower than that of salermide. Furthermore, MHY2256 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…This is in accordance with findings of Lara and coworkers [47], who showed that SIRT1inhibitors can induce massive apoptosis in p53-dependentcancers, but not in p53-independent cells. Our previous study showed the strongest induction of apoptosis in MCF-7 cells after treatment with salermide, a SIRT1 inhibitor, but SKOV3 cells showed only about a 10% increase in apoptosis [45,[48][49][50]. It appears that this observation in MCF-7 cells was due to the presence of the wild-type p53, since p53-deficient SKOV3 cells show only a small increase in apoptosis due to salermide [51].…”
Section: Discussionmentioning
confidence: 91%
“…This is in accordance with findings of Lara and coworkers [47], who showed that SIRT1inhibitors can induce massive apoptosis in p53-dependentcancers, but not in p53-independent cells. Our previous study showed the strongest induction of apoptosis in MCF-7 cells after treatment with salermide, a SIRT1 inhibitor, but SKOV3 cells showed only about a 10% increase in apoptosis [45,[48][49][50]. It appears that this observation in MCF-7 cells was due to the presence of the wild-type p53, since p53-deficient SKOV3 cells show only a small increase in apoptosis due to salermide [51].…”
Section: Discussionmentioning
confidence: 91%
“…Surgery is the main treatment for endometrial cancer. Most patients in the early stage can be cured by surgery, but treatment is limited for patients with metastasis and recurrence (23). It is widely recognized that laparoscopy is superior to laparotomy in most patients with endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A quinoxaline-based compound 4bb selectively reduces colon cancer cell viability without affecting normal fibroblasts (Ghosh et al, 2017). Moreover, MHY2256, a potent SIRT1 inhibitor, significantly inhibits growth of endometrial and breast cancer cells (De et al, 2018;. Recently, a new SIRT7 inhibitor (ID: 97491) has been identified that shows potent inhibitory effect on cancer growth by upregulating apoptosis (Kim et al, 2019).…”
Section: Targeting Nad + Consuming Enzymesmentioning
confidence: 99%
“…Recently, a new SIRT7 inhibitor (ID: 97491) has been identified that shows potent inhibitory effect on cancer growth by upregulating apoptosis (Kim et al, 2019). All these compounds work partially via promoting acetylation and activation of p53, thereby driving cell cycle arrest and inducing apoptotic or autophagic cell death (De et al, 2018;Ghosh et al, 2017;Kim et al, 2019;Tae et al, 2018).…”
Section: Targeting Nad + Consuming Enzymesmentioning
confidence: 99%